Analysis of kinematic and kinetic changes in scoliosis following spinal manipulation - Yanyun Gou; Lin Meng; Shaoqing Chen; Zheng Jiang; Huangwei Lei (Scientific Reports)
Abstract Scoliosis is a prevalent condition among adolescents, and the spinal manipulation is one of the conservative treatment methods for scoliosis patients. Impairment in movement function stands out as a typical characteristic in cases of scoliosis. This study utilized a single-arm clinical trial design involving 35 patients aged 18 to 20 with idiopathic scoliosis (IS) and Cobb angles ranging from 10° to 30°. The treatment protocol consisted of spinal manipulation sessions three times a week, each lasting 40 min, administered over a span of six weeks. Pre- and post-intervention assessments focused on the Cobb angle and lower limb kinematics and kinetics during functional movements such as level walking, stair ascent, and descent. Patients with IS showed improvements in the Cobb angle, as well as changes in lower limb kinematics and kinetics during functional activities, such as walking and stair navigation, following six weeks of spinal manipulation intervention. The study further demonstrated that spinal manipulation reduced lower limb’s sagittal joint mobility, increased stability in individuals with IS. Patients with IS exhibited significant changes in lower limb kinematics and kinetic following spinal manipulation, which may serve as a potential mechanism underlying the alteration of the Cobb angle. Future studies, particularly RCTs, are needed to further validate the effectiveness of spinal manipulation in treating IS.